The Representations of Inferiority Complex as Depicted on Virginia Woolf's 'The Duchess and The Jeweller' - Falsyawal Galang Smarandreetha; Fatimah Nurunnada Attamimi; Kusuma Wijaya; Rommel Utungga Pasopati (Jurnal Adijaya Multidisplin, 2023)
Virginia Woolf's short story entitled The Duchess and The Jeweller was first published in 1938. This short story reflects the England society era of significant change in the social class that brings many problems, especially in terms of social and economic statuses. Oliver Bacon, the main character, was born in poverty. Then, after working his way up, he eventually became the wealthiest jeweller in England. He also obsessed to move among aristocrats' circles just to satisfy his inferior feelings. Inferiority complex is a condition in which a person feels unable to do something valuable that makes the person feel inferior as stated by Alfred Adler. Then, how is the inferiority complex depicted in Oliver Bacon's character from Virginia Woolf's The Duchess and The Jeweller? Through qualitative method, this paper uses the perspective of inferiority complex to analyze Oliver Bacon’s problems when he climbs up to the social class and to demonstrate his inferiority complex because of his bad foretime. In conclusion, this paper gives proof that an inferiority complex can happen due to economic factors and make someone become a social climber.